(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
The self as an entity of being and becoming, is revealed as a dynamic process of constant change. The nature of this process as well as the structure of the self in Kierkegaard’s philosophy takes more than one shape as his thought evolves. This may be somewhat surprising. Isnʼt the self’s structure and its lineation essentially constant, while the content alone is the changing ingredient? This is not the case in Kierkegaard’s philosophy, where the very formation of the self changes (along with its content). In this paper I elaborate on Kierkegaard’s early view of the self’s structure. I then emphasize the dramatic change we find in Sickness unto Death, where the self is changed in both structure and content..